2013
DOI: 10.1002/asia.201300258
|View full text |Cite
|
Sign up to set email alerts
|

Structural Transformation between Supramolecular Nanofibers with Drastic Change of Conductivity by Heat and Ultrasound

Abstract: Transformation with every fiber of its being: Dehydrobenzoannulene derivatives with a boomerang shape, dipole moment, and substituents that make diverse interactions enable the construction of stimuli-responsive nanofibers despite the lack of stimuli-responsive groups in these compounds. Interestingly, the supramolecular nanofibers obtained after ultrasonic treatment displayed an 80% decrease in conductivity as compared to untreated nanofibers. This is the first example of an electronic wire for which the cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 52 publications
(13 reference statements)
0
9
0
Order By: Relevance
“…[139] Its symmetrical and planar p-conjugated structure induced the formation of self-assemblies, such as nanofibers and gels. [140][141][142][143][144][145] As expected from the highly strained structure,t he strain-promoted double azide-alkyne cycloadditiono f77 c takes place (Figure 31 c). [146] The electrophilic cyclization of 77 d using an excessa mount of iodine under oxygen atmosphere gave two types of diiododiones, 80 a and 80 b.…”
Section: Reviewmentioning
confidence: 81%
See 1 more Smart Citation
“…[139] Its symmetrical and planar p-conjugated structure induced the formation of self-assemblies, such as nanofibers and gels. [140][141][142][143][144][145] As expected from the highly strained structure,t he strain-promoted double azide-alkyne cycloadditiono f77 c takes place (Figure 31 c). [146] The electrophilic cyclization of 77 d using an excessa mount of iodine under oxygen atmosphere gave two types of diiododiones, 80 a and 80 b.…”
Section: Reviewmentioning
confidence: 81%
“…Dehydrobenzo[12]annulene 77 a was synthesized by Eglinton, Raphael, and co‐workers by using copper‐mediated coupling, and the strained structure was confirmed later by X‐ray crystallographic analysis of 77 b (∠ sp =165–167°) . Its symmetrical and planar π‐conjugated structure induced the formation of self‐assemblies, such as nanofibers and gels . As expected from the highly strained structure, the strain‐promoted double azide–alkyne cycloaddition of 77 c takes place regioselectively to give adduct 79 (Figure c) .…”
Section: Angle‐strained Alkyne‐containing π‐Conjugated Macrocyclesmentioning
confidence: 99%
“…The results reveal that all of the DBA derivatives formed SNFs (Figure 2d Ultrasound-induced supramolecular nanofibers of the DBAs: It was recently discovered that the SNFs of DBA 1 can be changed into other SNFs with different molecular arrangements by using ultrasound. [36] This implies that ultra- www.chemeurj.org sound can induce fibrous structures in the DBAs. In fact, fibrous materials of DBAs 2 and 3 were also formed by the sonication of amorphous powdered solids dispersed in 1,2-DCE.…”
Section: Resultsmentioning
confidence: 99%
“…Ultrasound‐induced supramolecular nanofibers of the DBAs : It was recently discovered that the SNFs of DBA 1 can be changed into other SNFs with different molecular arrangements by using ultrasound 36. This implies that ultrasound can induce fibrous structures in the DBAs.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, in 2009 we reported that a butadiynebridged acene-like pi-conjugated molecule so-called octadehydrodibenzo [12]annulene ( [12]DBA) derivative 14 possessing two methyl ester groups 1a (Scheme 1) exhibited excellent gelation ability under chlorinated solvents such as 1,2-dichloroethane. 15,16 The phenomenon is quite unusual because the compound has neither long substituent groups, steroidal groups, nor hydrogen bonding groups but just two methyl ester groups at noncentrosymmetric positions. Such a simple molecule, however, yielded an organogel successfully.…”
Section: Introductionmentioning
confidence: 99%